The attitudes of nurses towards mentally ill people in a general hospital setting in Durban - T. R. Mavundla; L. R. Uys (AOSIS, 1997)
A quantitative survey was undertaken to determine the attitudes of nurses towards mentally ill people at King Edward VIII Hospital, large academic hospital in Durban. Data were collected by a questionnaire intended to measure attitudes according to cognitive, affective and behavioral components in a sample of 100 black nurses. The results of this study were analyzed through a statistical software package, the statgraphic version 5.